A methodology for integration of ergonomics and total quality management for company strategies - Sancar Öğüş, İrem . (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Total Quality Management (TQM) and Ergonomics implementations in uni son contribute to the sustainability of the company and promote sustainable strategy. TQM and Ergonomics approaches do have common goals, but also diﬀer in some as pects. This study aimed to integrate these two approaches to achieve strategic company goals, mainly for manufacturing-based companies. In order to integrate these two ap proaches from a strategical point of view, ﬁrstly, critical success factors of TQM and Ergonomics were examined. Consequently, six main strategical objectives for compa nies and 25 factors of TQM and Ergonomics are determined to construct a hierarchical model. This model is solved by analytic hierarchy process (AHP) and fuzzy analytic hierarchy process (FAHP) methodologies. The data collected through a questionnaire from managers are analyzed to prioritize the critical success factors. Finally, the crit ical success factors of both approaches are then grouped to form four category and a conceptual model is suggested. Creating sustainable business is found to be the most important strategic objective, followed by proﬁt maximization and company credibil ity and reputation increase, respectively. Business process category is found to be the most important category, followed by managerial issues and leadership and customers, respectively. Quality increase is found to be the most important factor, followed by productivity and eﬃciency and continuous improvement, respectively.
Keywords: Total quality management.; Human engineering.